Single CpG site methylation controls estrogen receptor gene transcription and correlates with hormone therapy resistance. Issue 171 (July 2017) - Tsuboi, Kouki; Nagatomo, Takamasa; Gohno, Tatsuyuki; Higuchi, Toru; Sasaki, Shunta; Fujiki, Natsu; Kurosumi, Masafumi; Takei, Hiroyuki; Yamaguchi, Yuri; Niwa, Toshifumi; Hayashi, Shin-ichi
Highlights: Alteration of ERα expression occurred in AI resistant and related with acquired resistance. ERα promoter A dominantly influenced on regulation of ERα transcription. The region harboring promoter C had enhancer activity and single CpG (CpG4) methylation related with ERα transcription. CpG4 methylation level was inversely correlated with ERα positivity in breast cancer specimens. Abstract: Hormone therapy is the most effective treatment for patients with estrogen receptor α-positive breast cancers. However, although resistance occurs during treatment in some cases and often reflects changed estrogen receptor α status, the relationship between changes in estrogen receptor α expression and resistance to therapy are poorly understood. In this study, we identified a mechanism for altered estrogen receptor α expression during disease progression and acquired hormone therapy resistance in aromatase inhibitor-resistant breast cancer cell lines. Subsequently, we investigated promoter switching and DNA methylation status of the estrogen receptor α promoter, and found marked changes of methylation at a single CpG site (CpG4) in resistant cells. In addition, luciferase reporter assays showed reduced transcriptional activity from this methylated CpG site. This CpG region was also completely conserved among species, suggesting that it acts as a methylation-sensitive Ets-2 transcription factor binding site, as confirmed using chromatin immunoprecipitation assays. In estrogen receptor α-positive tumors, CpG4 methylation levels were inversely correlated with estrogen receptor α expression status, suggesting that single CpG site plays an important role in the regulation of estrogen receptor α transcription.